PENGARUH PERSONAL CONTROL DAN CULTURAL CONTROL TERHADAP EMPLOYEE PERFORMANCE PADA RUMAH SAKIT JIWA KOTA PEKANBARU - Kamilah, Faizah; Khairani, Zulia; Soviyanti, Efrita (Komunitas Manajemen Kompetitif, 2024)
This research aims to analyze the influence of the Management Control System (personal control and cultural control) on Employee Performance at the Pekanbaru City Mental Hospital. The data analysis method used is multiple linear regression, F test and t test are used to analyze the data. Data was obtained through a questionnaire method with a Likert scale. The independent variables in this research are personal control and cultural control. Meanwhile, the dependent variable is organizational performance. Data obtained with the help of SPSS 23 software. The results of this research are that personal control and cultural control have a significant influence on organizational performance Keywords: personal control, cultural control, employee performance